Letter of credit as import financing solution – an example of belarussian market - Krasitski, Stanislau (My University, 2010)
The research paper is divided into chapters, which gradually and consequently provide information necessary to understand nature and applicability of letter of credit. As the subject of research for my thesis I have chosen only one of methods – letter of credit. Not only because this financial tool balances the interests of all parties most effectively, but in my opinion, it possesses another significant feature, which represents the new evolutionary stage of the payment instruments. According to my own persuasion, letter of credit allows to drain credit capital more promptly, than regular bank credit. Additionally, it opens access for Belarusian institutions to cheap investment sources on favorable time and payment terms. Nowadays, banking specialists operating in the countries of emerging economy, including Belarus, are putting effort to adjust this unique financial instrument to their unstable market conditions. I believe that this research paper only partially presented all the benefits that can be achieved by proper and vise application of letter of credit in trade operations, since this financial device still conceals enormous potential …
Akredytywa jako narzędzie finansowania importu. Przykład rynku białoruskiego
Keywords: import; handel międzynarodowy; ryzyko handlowe; akredytywa